Gender differences in safety concerns and protective behaviors among men and women in Iceland - Freyja Vignisdóttir 2000- (2024)
Safety concerns, can stem from fears of physical, sexual, or psychological violence, leading individuals to adopt protective behaviors like avoiding threats and navigating public spaces cautiously. These concerns can cause stress and limit individuals’ freedom. Understanding this can help identify high-risk groups so community interventions can be made. Prior research show that perceived safety varies by gender and age, with women and older individuals generally exhibiting more safety concerns and protective behaviors. However, little is known about this among Icelandic students. This study examined gender and age differences in safety concerns and protective behaviors among 204 students (53.9% female) at Reykjavík University, aged 18-57. Linear regression analyses indicated that men reported significantly fewer safety concerns and protective behaviors than women (B=−1.45, p<.001). Older age groups (34-37 and 38-57) reported fewer safety concerns than the 18-21 age group. Additionally, age groups 30-33 and 34-37 showed less protective behavior than the 18-21 age group. These findings suggest that older age groups encounter fewer safety concerns and engage in less protective behavior (B=−1.50, p<0.001), though these results are less reliable than those related to gender. Despite Iceland's high safety ranking and gender equality, women still report significantly more safety concerns and protective behaviors than men. Keywords: Safety concerns, protective behavior, gender difference, violence, age difference Áhyggjur, sem snúa að eigin öryggi, geta stafað af ótta við líkamlegt, kynferðislegt eða andlegt ofbeldi. Þær gætu leitt til verndandi hegðunar (protective behavior) og t.d. birst í því að forðast ákveðna staði og vera stöðugt á varðbergi. Þessar áhyggjur geta því valdið streitu og takmarkað frelsi einstaklinga. Erlendar rannsóknir benda til þess að konur hafa almennt meiri áhyggjur af eigin öryggi og sýna meiri verndandi hegðun en karlar, einnig virðast þessar áhyggjur aukast með hækkandi aldri. Lítið ...